Efektifitas Penggunaan Video Pembelajaran Daur Ulang Limbah Plastik Untuk Meningkatkan Kreativitas Siswa Sekolah Dasar - Mohammad Syamsul Arifin; I Nyoman Lodra; Martadi Martadi (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The background of this research is the lack of utilization of plastic waste in the school environment, therefore video media for learning plastic waste recycling is needed so that students are more creative and not bored during lessons. The research method uses a qualitative descriptive method. Data analysis was used to compare the results of the pretest and posttest on the KKM scores of students before and after the use of plastic waste recycling learning videos in two elementary schools. As well as data collection using questionnaires and interviews taken from 20 elementary school students. The results of this study indicate that the use of plastic waste recycling learning videos is effective in learning, it is proven that there is an increase in the pretest-posttest results after using the media the average value is 83. In conclusion, the plastic waste recycling learning video media is very effective in learning in elementary schools, and can increase the creativity of students in utilizing plastic waste recycling.